Solving the Powertrain Puzzle 10th Schaeffler Symposium April 3/4, 2014 - Schaeffler Technologies GmbH & Co. KG (Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2014)
Every four years, Schaeffler provides an insight into its latest developments and technologies from the engine, transmission and chassis as well as hybridization and electric mobility sectors. In 2014 the Schaeffler Symposium with the motto "Solving the Powertrain Puzzle" took place from 3th to 4th of April in Baden-Baden. Mobility for tomorrow is the central theme of this proceeding. The authors are discussing the different requirements, which are placed on mobility in different regions of the world. In addition to the company's work in research and development, a comprehensive in-house mobility study also provides a reliable basis for the discussion. The authors are convinced that there will be a paradigm shift in the automotive industry. Issues such as increasing efficiency and advancing electrification of the powertrain, automatic and semi-automatic driving, as well as integration in information networks will define the automotive future. In addition, the variety of solutions available worldwide will become increasingly more complex and mobility patterns will also change rapidly. However, this does not mean that cars will drive virtually in the future. Powertrains based on internal combustion engines will still dominate for a very long time and demonstrate new strengths in combination with hybrid drives. Transmissions will also gain in importance as the link between the internal combustion engine and electric motor. The proceeding "Solving the Powertrain Puzzle" contains 34 technical papers from renowned experts and researchers in the field of automotive engineering. Mobility of the Future.- Powertrain Systems.- Developing Combustion Engines.- Double Clutch Systems.- Thermal Management.- Start Stop.- Chassis.- Range-Extender.- Hybrid Modules.- Wheel Hub Drives.- What Powertrains could learn from each other. Schaeffler with its product brands INA, LuK and FAG is a leading provider of rolling bearing and plain bearing solutions and of linear and direct drive technology, as well as a renowned supplier to the automotive industry of high-precision products and systems for engines, transmissions and chassis applications. With approximately 79,000 employees worldwide, Schaeffler is one of the largest German and European industrial companies in family ownership. With 170 locations in over 49 countries, Schaeffler has a worldwide network of manufacturing locations, research and development facilities, sales companies, engineering offices and training centers.